answersLogoWhite

0


Best Answer

5x + 9y = 0
6x + 6y = 2 use substitution method

5x + 9y = 0
y = -5x/9

6x + 6y = 2 substitute y with -5x/9
6x + 6(-5x/9) = 2
6x - 30x/9 = 2 multiply by 9 to both sides
54x - 30x = 18
24x = 18
x = 24/18 = 4/3

y = -5x/9 = (-5/9)x substitute x with 4/3
y = (-5/9)(4/3) = -20/27

Thus the solution is x = 4/3 and y = -20/27.

User Avatar

Wiki User

โˆ™ 2009-10-23 01:37:18
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
840 Reviews

Add your answer:

Earn +20 pts
Q: 5x plus 9y equals 0 6x plus 6y equals 2?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked